Producing criminality: The expanding power of crime analysts - Ballucci, Dale (Crime, law and social change, 2023)
Crime analysts play a central role in producing and justifying reasonable suspicions of future criminality. Despite the governing power of these agents, little is known about how they use data to determine risk. My investigation examines the local decision-making practices of crime analysts in producing the Prolific Offender List. Using interview data from analysts in a Canadian jurisdiction, I detail and problematize the production of the 'prolific offender.' I demonstrate the limitations of police databases and how crime analysts account for these limitations using their professional judgment.